Carboxymethyl cellulose capsulated zein as pesticide nano-delivery system for improving adhesion and anti-UV properties. (1st March 2020) - Hao, Li; Lin, Guanquan; Lian, Jiajia; Chen, Long; Zhou, Hongjun; Chen, Huayao; Xu, Hua; Zhou, Xinhua
Graphical abstract: Highlights: P-Zein incorporated with CMC and DMDAAC is prepared by electrostatic interaction. P-Zein/CMC-g-PDMDAAC is applied to form nano-controlled release pesticide system. AVM@P-Zein/CMC-g-PDMDAAC presents excellent adhesion and anti-UV properties. Such system can control pesticide release by triggered monomer ratio and pH. Abstract: In order to further enhance hydrophilicity of zein and achieve nano-scale pesticide system, phosphorylated zein (P-Zein) was incorporated with graft copolymer CMC-g-PDMDAAC by electrostatic interaction, in which carboxymethyl cellulose (CMC) and diallyldimethylammonium chloride (DMDAAC) as monomers. P-Zein/CMC-g-PDMDAAC was applied to encapsulate model pesticide avermectin (AVM) via electrostatic interaction to achieve AVM@P-Zein/CMC-g-PDMDAAC nano-pesticides. The stability, drug loading, anti-ultraviolet, adhesion, sustained-release and toxicity of nano-pesticides presented considerable behavior confirmed via various characteristics. The results indicated that AVM@P-Zein/CMC-g-PDMDAAC had an average particle size of 360 nm, and possessed favorable dispersion performance and excellent anti-ultraviolet property compared to P-Zein. And comparatively, encapsulation efficiency increased up to 82.11%. In addition, adhesion performance of AVM@P-Zein/CMC-g-PDMDAAC on foliage also improved by about 20% compared to P-Zein. Also, AVM@P-Zein/CMC-g-PDMDAAC can intelligently control pesticide release by adjusting monomer ratio and pH values. More importantly, such nano-pesticide system presented no significant difference on toxicity in comparison with bare AVM.